'Saved from the sordid axe': representation and understanding of pine trees by English visitors to Italy in the eighteenth and nineteenth century. (2nd July 2016) - Piana, Pietro; Watkins, Charles; Balzaretti, Ross
ABSTRACT: Pine trees were frequently depicted and celebrated by nineteenth-century English artists and travellers in Italy. This paper examines how British visitors gained knowledge of Italian trees through drawings, paintings and prints, before and during their visits to Italy. It considers knowledge of pines by late eighteenth- and early nineteenth-century authorities such as William Gilpin and John Claudius Loudon and then focuses on the representation and understanding of pines in three contrasting sites: the pines of Rome, the coastal pines of Liguria and finally the famous pine wood of Ravenna. These trees were also an important element of local agriculture and the authors combine the analysis of local land management records, paintings and travellers' accounts to reclaim differing understandings of the role of the pine in nineteenth-century Italy.